FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Prajitno, Sugiarto; Vionita (School of Accountancy, University of Agung Podomoro, 2020)
The intent of this research is obtained empirical evidence related to several factors thatinfluence earnings management. The independent variable used in this research are firm size, firm age,firm financial leverage, audit quality, board of director, board of commissioner, audit committeemeetings, managerial ownership, profitability, and firm growth, with the dependent variable earningsmanagement. Non financial companies listed on the Indonesia Stock Exchange(BEI) during 2014 until2018 are the object of this research. The data used are secondary data (financial statement and annualreport) from www.idx.co.id. Purposive sampling method is used in the sample selection. Sixty twocompanies which match the criteria are used as the research sample. This research use multipleregression in observing the effect of each variable. The results of this research indicate that firm size,firm age, board of commissioner, and firm growth influence earnings management. While firmfinancial leverage, audit quality, board of director, audit committee meetings, managerial ownership,and profitability do not affect earnings management.